Transmission mechanisms of the Merah Putih Village cooperative's multiplier effect on the local economy: A conceptual analysis - Daniel Simamora (Privietlab, 2025)
The Merah Putih Village Cooperative (KDMP) program is a strategic program initiated by the Indonesian Government to accelerate economic development starting from the village level, aligned with the national long-term development plan agenda. Although this program has significant potential for economic impact, a fundamental understanding of its transmission mechanisms to the local economy remains limited. This study aims to analyze and formulate a conceptual model that maps the multiplier effect transmission mechanisms generated by the KDMP. Using a qualitative method through a systematic literature review, this study identifies and synthesizes various pathways of cooperative economic impact on the local economy. The study results show that KDMP, with its business model, creates multiplier effects through three primary transmission pathways. First, the input provision and consumption. The second is financial intermediation and investment, and the third is value chain aggregation and integration. These pathways collectively generate reinforcing direct, indirect, and induced multiplier effects. This study also formulates a conceptual framework that can serve as an analytical tool for policymakers to design effective support interventions and as a foundation for future research to measure the actual magnitude of the KDMP’s multiplier effect.